Clinical, parasitological and immunological aspects of experimental infection with Trypanosoma evansi in dogs - Aquino, Lúcia Padilha Cury Thomaz de [UNESP]; Machado, Rosangela Zacarias [UNESP]; Alessi, Antônio Carlos [UNESP]; Marques, Luiz Carlos [UNESP]; Castro, Márcio Botelho de [UNESP]; Malheiros, Euclides Braga [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1999)
This research investigated the pattern of antibody response by means of enzyme linked immunosorbent assay (Elisa) and indirect fluorescent antibody test (IFAT) through the course of experimental Trypanosoma evansi infection in dogs. Clinical and parasitological features were also studied. The average prepatent period was 11.2 days and parasitaemia showed an undulating course. Biometrical study of parasites revealed a mean total length of 21.68mm. The disease was characterized by intermittent fever closely related to the degree of parasitaemia and main clinical signs consisted of pallor of mucous membrane, edema, progressive emaciation and enlargement of palpable lymph nodes. Diagnostic antibody was detected within 12 to 15 days and 15 to 19 days of infection by IFAT and Elisa, respectively. High and persistent antibody levels were detected by both tests and appeared not to correlate with control of parasitaemia
Keywords: Trypanosoma evansi; Dog; biometry; ELISA; inmunofluorescent antibody test; clinical features